Applicabillity of teaching techniques fot the first pedagogical stage in a class of english as a second languaje for students of fourth level at Antonio Ríos Saavedra Elementary School, Boquerón - Chiriquí, 2013 - Saldaña, Darling; Castillo, Kathia (David, Panamá : UDELAS, 2013)
This project intends to provide practical teaching techniques to be used at the three pedagogical stages in an english class, which it perfoms on its best anda the viable way, including relevant details such as the activities and resources, pertinent within a class.
GENERAL INDEX Figures index Graphic index Introduction CHAPTER I: STATEMENT OF THE PROBLEM CHAPTER II: THEORETICAL FRAMEWORK 2.1. Techniques for the development of the first stage of a class 2.1.1. Technique concept 2.2. Classification of techniques for the beginning stage 2.2.1. Classification of beginning stage techniques 2.2.1.1. Motivational techniques 2.2.1.2. Diagnostic techniques 2.2.1.3. Techniques for introduction 2.2.1.4. Discussion techniques 2.2.2. Teaching techniques according to its way of application 2.2.2.1. Group (teamwork) technique 2.2.2.2. Individual (personal) technique 2.2.2.3. Digital (technological) techniques 2.3. Methodological factos which affect the beginning techniques 2.3.1. Competency model concepts 2.3.2. Competence model implications 2.3.3. Categories of the competenncies 2.3.4. Areas of the competencies 2.3.5. Types of competences 2.3.5.1. Basic competences 2.3.5.2. Generic competences 2.3.5.3. Specific competences 2.4. Techniques and strategies differences 2.5. Advantages versus disadvantages of techniques 2.6. Factors that affect the first stage development class 2.6.1. Discipline 2.6.1. Techniques to improve discipline 2.6.2. Space 2.6.3. Time 2.6.4. Resources availability 2.7. Compendium of activities CHAPTER III: METHODOLOGY OF THE INVESTIGATION CHAPTER IV: ANALYSIS AND INTERPRETATION OF RESULTS CONCLUSION AND RECOMMENDATION REFERENCES ANNEXES
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; ANTONIO RÍOS SAAVEDRA ELEMENTARY SCHOOL, BOQUERÓN - CHIRIQUÍ